MAP4K4 MEDIATES CARDIOMYOCYTE CELL DEATH AND POTENTIATES A HEART FAILURE PHENOTYPE. (21st November 2014) - Fiedler, LR; Jenkins, M; Maifoshie, E; Harada, M; Stuckey, DJ; Song, W; Sampson, R; Harding, SE; Schneider, MD
Abstract : Rationale: Cardiomyocyte cell death plays a causal role in heart failure therefore its inhibition poses a promising therapeutic approach. However, investment is undermined due to poor translation and cardiotoxicity. Here, we describe validation of a potential target; mitogen activated protein 4 kinase kinase kinase kinase (MAP4K4). Methodology/Results: 4 weeks pressure overload (TAC; transverse aortic constriction) in alphaMyHC-MAP4K4 mice (cardiomyocyte-specific over-expression) induced apoptosis (3.60 %+1.01 TUNEL-positive cardiomyocytes, n=5, p<0.05 to wildtype (WT) littermates; 0.53 %+0.19, n=5). Peri-vascular fibrosis and upregulation of autophagy markers Beclin1 and LC3 (associated with heart failure) was evident only in TG-TAC mice (p<0.05 to WT-TAC). Systolic function assessed by pressure-volume loops (shams n=6, TAC-TG n=9, TAC-WT n=10) showed unaffected contractility and compliance in WT-TAC mice although relaxation was impaired (Tau, p<0.05). In contrast, TG-TAC mice had significantly impaired compliance (Emax, p<0.01), contractility (Ees-ESPVR, p<0.01) and relaxation (Tau, p<0.01). Inhibition of MAP4K4, by siRNA-mediated knockdown or pharmacologically (selective in-house novel compound; 5 out of 141 kinases inhibited) was cardioprotective in rat neonatal and human iPSC-derived cardiomyocytes subjected to oxidative stress (H202) or C2-ceramide (measured by loss of membrane integrity, Caspase 3 activity, hypodiploid DNA). Conclusions: MAP4K4 drives cardiomyocyte cell death and dysfunction, thus poses an attractive target in heart failure. Our novel compound, validated in human and mouse models, represents a start-point for further development with improved translational potential.